STATE AID FOR ENVIRONMENTAL PROTECTION ON SUPRANATIONAL LEVEL AND IN DOMESTIC LAW - Fišer-Šobot, Sandra; Divljak, Drago (Zbornik radova Pravnog fakulteta u Novom Sadu, 2018)
In contemporary society environmental protection plays a significant role. Activities of relevant entities on supranational and national level interwine in achieving the goal of effective environmental protection. The role of the state in environmental protection is of exceptional importance and can be materialized in different ways. A state can provide different financial incentives for environmental protection and their utilisation is regulated on both supranational and national level. On international level this area is governed by rules regulating subsidies and on EU and national level by rules regulating state aid for environmental protection. This paper examines relevant WTO provisions on subsidies, EU rules and domestic rules on state aid for environmental protection.